2018
DOI: 10.3389/fmars.2018.00374
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Light Availability and Prey Type on the Growth and Photo-Physiological Rates of the Mixotroph Noctiluca scintillans

Abstract: Gomes et al.Photophysiology of Mixotroph Noctiluca scintillans concentrations (0.005-0.08 µM NH 4 + cell −1 ) was obtained under low light conditions. For P. tricornutum and T. weissflogii fed cultures under light limitation, NH 4 + continued to increase past the 14-day period suggesting a strong and efficient mechanism for regulation of intracellular nutrients by Noctiluca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
(88 reference statements)
0
17
0
Order By: Relevance
“…Secondly, our earlier work had ascribed the advent of Noctiluca blooms to the upshoaling of hypoxic waters in the euphotic zone 35 , caused by a possible expansion of the AS's permanent oxygen minimum zone (OMZ) 45 . In this study 35 , we showed using shipboard experiments in which natural populations were exposed to suboxic seawater 36 that endosymbionts in Noctiluca cells photosynthesized more efficiently under suboxic conditions. More recent studies 33,34,39 , have attributed the advent of Noctiluca blooms to acute "silicate stress", a situation that would prevent diatom populations from attaining bloom proportions, particularly in the northwestern AS where they have been the predominant algal group in the past 28,29,32,46 .…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Secondly, our earlier work had ascribed the advent of Noctiluca blooms to the upshoaling of hypoxic waters in the euphotic zone 35 , caused by a possible expansion of the AS's permanent oxygen minimum zone (OMZ) 45 . In this study 35 , we showed using shipboard experiments in which natural populations were exposed to suboxic seawater 36 that endosymbionts in Noctiluca cells photosynthesized more efficiently under suboxic conditions. More recent studies 33,34,39 , have attributed the advent of Noctiluca blooms to acute "silicate stress", a situation that would prevent diatom populations from attaining bloom proportions, particularly in the northwestern AS where they have been the predominant algal group in the past 28,29,32,46 .…”
Section: Resultsmentioning
confidence: 89%
“…3b,c) is unparalleled for any open ocean ecosystem. In this nutrient-poor scenario, we contend that as with other mixotrophs 48 , Noctiluca's dual mode of obtaining nutrients 36 , confers upon it a significant competitive advantage over autotrophic phytoplankton especially when nutrients are limiting. When feeding on external prey, Noctiluca accumulates large amounts of nitrogen as ammonium (0.003-0.012 μM NH 4…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations